Effects of social media on smartphone use before and during velocity-based resistance exercise on cognitive interference control and physiological measures in trained adults. Issue 5 (3rd September 2022) - Fortes, Leonardo Sousa; Lima Júnior, Dalton; Costa, Yago Pessoa; Albuquerque, Maicon Rodrigues; Nakamura, Fabio Yuzo; Fonseca, Fabiano Souza
Abstract: The purpose is to analyze the effect of social networks on smartphones before and during velocity-based resistance exercise on the internal training load, heart rate variability (HRV), and cognitive interference control. Twelve trained adults volunteered to participate in this randomized and crossover design research study with three experimental conditions. The participants randomly performed a resistance exercise session, watching TV before (CON) the session or using social networks on a smartphone prior to (30SMA-P) and intra-session (SMA-INT). The participants underwent sets with repetitions [15RM load] up to 20% mean velocity loss. HRV indicators and cognitive interference control were measured before and 30-min after each experimental session. Internal training load was evaluated 30-min after each experimental session, which was calculated by the product between resistance exercise volume and RPE. No condition versus time interaction for HRV indicators ( p  > 0.05) was observed. It was not revealed a condition versus time interaction for cognitive interference control ( p  > 0.05). No condition effect for internal training load ( p  > 0.05) was observed. It was concluded that 30-min of social networks on smartphones before or intra-session resistance exercise had no effects on HRV indicators, cognitive interference control, and internal training load in trained adults.